MANDEJA (ALAT PEMANFAATAN AIR DAN DEBIT HUJAN) SEBAGAI SOLUSI KETERSEDIAAN AIR SEHAT LAYAK KONSUMSI - Panji Imantama Riyadi (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The author created the Mandeja Tool to address current environmental issues, especially regarding water, so that water suitable for consumption can be produced at low cost and with materials that are cheap and easy to obtain. Mandeja uses waste and produces no waste in the manufacturing process. Mandeja is a practical tool, energy efficient, and does not have any risks in its use because it is made from natural ingredients without adding dangerous chemicals. Mandeja is also suitable for use anywhere, especially in households. Mandeja is made from inorganic waste so that it can reduce the volume of waste piled up in Wonogiri. Mandeja utilizes the principles of filtration and electrolysis. Mandeja uses Moringa seeds to coagulate water that is not suitable for consumption, such as river water, into water that is suitable for consumption because Moringa seeds can be used as a quick and simple method to clean dirty river water. Research shows that this simple coagulation method not only reduces water pollution but also harmful bacteria. The moringa powder combines with the solids in the water and sinks to the bottom. This treatment removes 90-99% of the bacteria contained in the water. Mandeja also uses the principle of electrolysis which can change the pH of water to alkaline (close to 8) which has many benefits for the body. Water that is not suitable for drinking is coagulated first using moringa seeds. Then, the filtered water is electrolyzed in Mandeja to obtain alkaline water which is good for body health. The Mandeja water processing system produces healthy water suitable for consumption because Mandeja uses moringa seed coagulation and the principle of electrolysis.